Building metadata architectures: a case for e–research. (27th October 2014) - Sgouropoulou, Cleo; Koutoumanos, Anastasios
This paper describes a semi–structured approach for the development of metadata architectures to facilitate the description, dissemination and reuse of interlinked resources within a federation of open access repositories. This approach, building upon the methodology and components of the Singapore Framework for Dublin Core Application Profiles, results in rich metadata architectures that bundle together functional requirements, domain model(s), a description set profile, usage guidelines and data formats. Maximum interoperability, reuse of existing mature metadata standards, long–term quality control and extensibility for addressing further community needs constitute the main benefits of such metadata architectures. The paper details the phased implementation of the proposed approach, along with a specific case study, based on a European–wide research initiative to deploy a community–focused integrated platform for the retrieval of open content, supporting explicit models of the scholarly life cycle and the practical tasks targeted by the agricultural research domain.